The Effect of Physical Education Learning Using Modified Balls on Basketball Passing Learning Outcomes among Junior High Students - Ramadhan, Hafidz Mukti; Nurrochmah, Siti; Singh, Balwant (Media Ilmu Keolahragaan Indonesia, 2024)
Abstract. The research aims to investigate the effect of modified balls on basketball passing learning outcomes among students at SMP Negeri 1 Salam Babaris. The study examined how different types of balls regular basketballs, volleyballs, and rubber balls influence students’ learning performance in passing activities during physical education classes. A one-way analysis of covariance (ANCOVA) was applied to compare the effects of each modification. The participants were students enrolled in basketball passing lessons at SMP Negeri 1 Salam Babaris. Data were collected through a basketball passing test against a wall and observation of learning implementation. Statistical analysis using ANCOVA indicated that the type of ball used in learning significantly influenced basketball passing performance. The calculated F-value of 5829.15 exceeded the F-table value of 3.02 at the 0.05 significance level, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (Hₐ). The findings revealed that using volleyball and rubber balls in learning activities produced higher passing scores compared to using standard basketballs. The adaptation of learning media through modified balls enhanced students’ ability to perform accurately and controlled passes. The interpretation of the results suggests that instructional modification in physical education can foster engagement, motivation, and motor skill mastery. The research contributes to the development of effective teaching strategies in physical education by emphasizing that appropriate equipment modification can improve student performance and facilitate successful skill acquisition in basketball passing. Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan bola yang dimodifikasi terhadap hasil belajar passing bola basket pada peserta didik di SMP Negeri 1 Salam Babaris. Penelitian ini menelaah bagaimana berbagai jenis bola seperti bola basket standar, bola voli, dan bola karet mempengaruhi performa belajar peserta didik dalam aktivitas passing selama pembelajaran pendidikan jasmani. Metode penelitian yang digunakan adalah eksperimen komparatif dengan analisis kovarians satu arah (ANCOVA). Partisipan dalam penelitian ini adalah peserta didik yang mengikuti pembelajaran passing bola basket di SMP Negeri 1 Salam Babaris. Data dikumpulkan melalui tes passing bola basket ke dinding dan lembar observasi pelaksanaan pembelajaran. Hasil analisis statistik menggunakan ANCOVA menunjukkan bahwa jenis bola yang digunakan dalam pembelajaran berpengaruh signifikan terhadap kemampuan passing bola basket. Nilai Fhitung sebesar 5829,15 lebih besar daripada Ftabel sebesar 3,02 pada taraf signifikansi 0,05, sehingga hipotesis nol (H₀) ditolak dan hipotesis alternatif (Hₐ) diterima. Temuan penelitian menunjukkan bahwa penggunaan bola voli dan bola karet dalam kegiatan pembelajaran menghasilkan skor passing yang lebih tinggi dibandingkan penggunaan bola basket standar. Adaptasi media pembelajaran melalui modifikasi bola terbukti meningkatkan kemampuan peserta didik dalam melakukan passing secara lebih akurat dan terkontrol. Interpretasi hasil penelitian ini menunjukkan bahwa modifikasi instrumen pembelajaran dalam pendidikan jasmani dapat meningkatkan keterlibatan, motivasi, dan penguasaan keterampilan gerak peserta didik. Penelitian ini berkontribusi terhadap pengembangan strategi pembelajaran efektif dalam pendidikan jasmani dengan menekankan bahwa modifikasi peralatan pembelajaran yang tepat dapat meningkatkan performa belajar dan keberhasilan peserta didik dalam menguasai keterampilan passing bola basket.